NURSING IN THE EMPOWERMENT OF THE FAMILY CAREGIVER OF THE AGED IN HOME CONTEXT: A SCOPING REVIEW - Nóbrega, Tercio (2020)
Introduction: The demographic aging and the changes of the epidemiological pattern are leading to new necessities in terms of health. Most of the times, it is the family caregiver who assures the care delivery. It is imposed, therefore, an evaluation that intertwines family, the caregiver and the person who needs to be taken care of. Objective: Identify the nursing strategies in the empowerment of the family caregiver of the aged person in the home context. Methods: A scoping review was developed with the following question: what are the nursing strategies in the empowerment of the family caregiver to the aged person in the home context? Population: family caregiver of the dependent aged person; Concepts: nursing; empowerment; family caregiver; dependent aged person; Context: home. The studies to be included are quantity, quality and mixed. The research was accomplished with the MeSH descriptors intertwined by the Boolean AND as well as OR combining the following research strategy: Nurs* AND Empowerment OR Aged AND Caregivers. It proceeded the research of primary and secondary articles, published in ProQuest and PubMed databases and in the EBSCOhost platform: CINAHL Complete, Nursing & Allied Health Collection: Comprehensive, MEDLINE Complete and Mediclatina, with its regulators: full text, published between 01/01/2014 and 31/11/2018, human beings, age group: 19+ years and any author who is a nurse. Results: The study selection process was developed according to the PRISMA, proposed by the Joanna Briggs Institute, assuring the methodological quality of it. In these results arises the necessity of using new and innovated strategies to support the caregivers, promoting their empowerment and enabling them for the care. Conclusions: The obtained evidences indicate that the intervention of the nurse at home encourages the empowerment of the family caregiver, reducing the anxiety and stress, improving the general domains of physical and mental health, enabling them to care.